Method for separating metal molybdenum and rhenium from nickel-based superalloy electrochemical dissolving solution
By adjusting the pH value in the electrochemical dissolving solution of nickel-based high-temperature alloy and using modified resin adsorption, the problems of low recovery and low purity in the separation process of rhenium and molybdenum are solved, and efficient enrichment and purity of rhenium and molybdenum are achieved. It has the advantages of environmental protection, economical and energy-saving.
Patent Information
- Application Number
- CN202411696793.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-26
AI Technical Summary
In the existing rhenium and molybdenum separation processes, due to the similar chemical properties of the two, the recovery rate, low purity and complex process, making it difficult to effectively separate and recover the rare metal rhenium.
By adjusting the pH value in the electrochemical dissolving solution of nickel-based high-temperature alloy, using the specific adsorption effect of the modified resin, adsorbing and desorbing rhenium and molybdenum respectively, the multi-step evaporation concentration and recrystallization process is adopted to improve the recovery rate of rhenium and molybdenum and purity.
It has achieved efficient enrichment and purity improvement of rhenium molybdenum, and its process is simple and practical. It has the advantages of environmental protection, economical, energy-saving and high resource utilization, reducing the energy consumption and waste emissions of the process.
Smart Images

Figure CN119177366A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy, and in particular relates to a method for separating metallic molybdenum and rhenium from an electrochemical dissolution solution of a nickel-based high-temperature alloy. Background Art
[0002] Rhenium, a rare metal with a high melting point, has important applications in cutting-edge high-tech fields such as aerospace, nuclear energy, and electronics. Research on its extraction and recovery technologies is crucial for its application.
[0003] Metal molybdenum has the advantages of high strength, high melting point, corrosion resistance, and abrasion resistance, and has been widely used in industry. In recent years, the application of molybdenum in high-tech fields has continued to expand, such as machinery, automobiles, aerospace, aviation, space development, petrochemicals, food, anti-corrosion, plastics, composite materials, vacuum engineering, chemical industry, electrical and electronic technology, metallurgical machinery, medicine, agriculture, etc.
[0004] Rhenium and molybdenum are relatively rare metallic elements in the Earth's crust, and their natural distribution and concentration have a significant impact on their extraction processes. Rhenium often coexists with metallic minerals such as molybdenum and copper, and is particularly abundant in porphyry copper and molybdenum ores. However, due to its extremely low abundance, typically only a few parts per million, direct extraction of rhenium from its ores is extremely challenging.
[0005] In existing extraction processes, the separation of molybdenum and rhenium is a key step. Due to the similarities in their chemical properties, such as similar ionic radius, charge state, and solubility in certain solvents, they easily interfere with each other during the separation process. The main methods for recovering rhenium include precipitation, extraction, and ion exchange. The ion exchange method is suitable for recovering rhenium from solutions with low ion concentrations, is environmentally friendly, and can be reused. However, the main impurity elements molybdenum and rhenium in the solution have very similar properties, resulting in a low rhenium-molybdenum recovery rate in the ion exchange method, a complex process flow, and low purity of the recovered rhenium. Summary of the Invention
[0006] The present invention provides a method for separating metallic molybdenum and rhenium from an electrochemical solution of a nickel-based high-temperature alloy. By controlling the differences in the ionic forms of molybdenum and rhenium under the pH value of the solution and utilizing the specific adsorption effect of a modified resin, characteristic adsorption of rhenium and molybdenum is achieved, thereby improving the recovery rate and purity of rhenium and molybdenum. The process is simple, practical, and easy to promote.
[0007] A method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution, the specific steps of which are as follows: (1) Adjusting pH: Using sodium carbonate solution to adjust the pH value of the rhenium-molybdenum solution to 0-1.5; (2) Molybdenum resin adsorption / desorption: The rhenium-containing molybdenum solution whose pH value is adjusted in step (1) is adsorbed by a modified MTS9570 resin, wherein the modified MTS9570 resin is obtained by modifying the MTS9570 resin with a phosphoric acid solution, and a molybdenum adsorption liquid is obtained; then, phosphoric acid and sulfuric acid solutions are used as eluents to elute the modified MTS9570 resin to obtain a molybdenum eluent, which is returned to step (1) to the rhenium-containing molybdenum solution; and then, an ammonia solution is used to desorb the modified MTS9570 resin after the eluent to obtain a molybdenum desorption liquid; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5-1.5 with sulfuric acid solution, and the modified MTA1721 resin is adsorbed thereon, wherein the MTA1721 resin is obtained by modifying the MTA1721 resin with a secondary amine; the modified MTA1721 resin is then eluted with sulfuric acid solution as an eluent to obtain a rhenium eluent, and the solution is returned to step (1) to the rhenium-containing molybdenum solution; the modified MTA1721 resin after elution is first desorbed with an ammonium sulfate and ammonia water mixture, wherein the mass concentration of ammonium sulfate in the ammonium sulfate and ammonia water mixture is 10% and the mass concentration of ammonia water is 0.1%, to obtain a first-stage rhenium desorption solution, and the solution is returned to step (1); the modified MTA1721 resin after the first-stage desorption is then desorbed with an ammonia water solution to obtain a second-stage rhenium desorption solution; (4) Evaporation concentration and crystallization: the molybdenum desorption solution obtained in step (2) is evaporated and concentrated to 1 / 3 of the volume of the molybdenum desorption solution at 120° C. to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 0-1.5, and returned to step (2) to the rhenium-containing molybdenum solution with adjusted pH value; the second-stage rhenium desorption solution obtained in step (3) is evaporated and concentrated to 1 / 3 of the volume of the second-stage rhenium desorption solution at 120° C. to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 0.5-1.5, and returned to the solution after the molybdenum adsorption in step (3); (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are dissolved in ultrapure water respectively, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor respectively; the secondary crystallized ammonium molybdate mother liquor is returned to the molybdenum desorption solution of step (4); the secondary crystallized ammonium rhenate mother liquor is returned to the second-stage rhenium desorption solution of step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, and hydrogen is introduced for high-temperature calcination at a temperature of 650°C to prepare metallic molybdenum and metallic rhenium.
[0008] Furthermore, the preparation process of the modified MTS9570 resin is as follows: the cleaned MTS9570 resin is soaked in sulfuric acid for 2 hours, washed with distilled water until the discharged water is close to neutral, then soaked in phosphoric acid solution for 12 hours, and washed with water until the pH of the discharged water is 6, and drained.
[0009] Furthermore, the concentration of the sulfuric acid is 2 mol / L, and the amount of the sulfuric acid used is 3-5 times the volume of the resin; the concentration of the phosphoric acid solution is 2 mol / L, and the amount of the phosphoric acid solution used is 3-5 times the volume of the resin.
[0010] Furthermore, the preparation process of the modified MTA1721 resin is as follows: soaking the cleaned MTA1721 resin in a secondary amine for 12 hours, washing with water until the discharged water is neutral, and draining the water.
[0011] Furthermore, the amount of the secondary amine is 3-5 times the volume of the resin.
[0012] Furthermore, the rhenium-molybdenum-containing solution is a nickel-based high-temperature alloy electrochemical dissolution solution.
[0013] Furthermore, the mass concentration of the ammonia solution in step (2) and step (3) is 10%; the amount of the ammonia solution is 3 times the volume of the desorbed resin, and the hourly flow rate of the ammonia solution is 2-4 times the volume of the resin.
[0014] Furthermore, in step (2) and step (3), the pH of the eluent sulfuric acid solution is 2; the amount of sulfuric acid solution used is 5 times the volume of the resin to be eluted, and the hourly flow rate of the sulfuric acid solution is 4 times the volume of the resin.
[0015] Furthermore, the dosage of the ammonium sulfate and ammonia water mixture is 10 times the volume of the MTA1721 resin, and the hourly flow rate of the ammonium sulfate and ammonia water mixture is 1-2 times the volume of the resin.
[0016] Furthermore, in step (1), the mass concentration of the sodium carbonate solution is 9%, and in steps (3) and (4), sulfuric acid solution is used to adjust the pH value.
[0017] Advantages and positive effects of the present invention: 1. The present invention adopts the resin adsorption method, and the rhenium and molybdenum in the solution are converted into ReO4 - and MoO4 2- The anionic form of Mo exists. When pH is less than or equal to 2.5, Mo exists in the form of cation. The phosphoric acid chelation of molybdenum resin makes the resin more selective for molybdenum. At the same time, the secondary amine impregnation of rhenium resin makes the resin more selective for rhenium.
[0018] 2. The present invention adopts a method of resin grafting functional groups to improve the selectivity of the two resins for rhenium and molybdenum, so it can treat various acidic nickel-based high-temperature alloy electrochemical dissolution solutions and use a wide range of raw materials.
[0019] 3. After the rhenium and molybdenum in the solution are effectively enriched, the molybdenum resin is directly desorbed with ammonia water to obtain ammonium molybdate. About 5% of the molybdenum is not adsorbed by the molybdenum resin and enters the rhenium resin. The desorption of the rhenium resin is divided into two stages. The first stage uses 0.1% ammonia water + 10% ammonium sulfate to desorb the molybdenum. The resulting desorbed liquid is acidified and then further adsorbed by the molybdenum resin. The second stage uses 10% ammonia water to desorb ammonium perrhenate. The purity of ammonium molybdate is 99.8%, and the purity of ammonium rhenate is 99.9%.
[0020] 4. High-purity ammonium molybdate and ammonium perrhenate are obtained by evaporation, concentration and recrystallization, with purities of 99.99% and 99.999% respectively.
[0021] 5. The reasonable process combination of the present invention enables rhenium and molybdenum to be recovered and effectively utilized, achieving the goals of environmental protection, economy, energy saving, and high resource utilization. The ion exchange resin process used has low energy consumption, and the entire process basically does not emit three wastes. All resources are utilized with maximum efficiency, and the resulting products are convenient for subsequent treatment and processing. Therefore, the present invention has the advantages of environmental protection, economy, energy saving, and high resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 1 is a process flow chart of an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0024] The following adsorption rate calculation method Calculation of adsorption process: Taking molybdenum as an example, the concentration of molybdenum in the feed solution (C0, mg / L), the concentration of molybdenum in the solution after molybdenum adsorption (C1, mg / L), and the concentration of molybdenum in the solution after desorption (C2, mg / L) were determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the adsorption rate E of molybdenum was calculated using formula (1-1).
[0025] The following embodiment of the method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy can be found in the process flow chart. Figure 1 .
[0026] Example 1 The high-temperature alloy leachate of a high-temperature alloy recycling plant, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment, contains the following main elements: nickel 80 g / L, cobalt 3.6 g / L, aluminum 3.2 g / L, chromium 2.8 g / L, rhenium 1.8 g / L, molybdenum 1.2 g / L, tantalum 20 mg / L, and tungsten 120 mg / L.
[0027] Preparation method of modified MTS9570 resin: MTS9570 resin is repeatedly washed with 50-60℃ hot water. After filtration, the resin is soaked in 2mol / L sulfuric acid for 2 hours (the amount of sulfuric acid is 5 times the volume of the resin), washed with distilled water until the effluent is nearly neutral, then soaked in 2mol / L phosphoric acid solution for 12 hours (the amount of phosphoric acid solution is 5 times the volume of the resin), and washed with distilled water until the pH of the effluent is 6, and then drained. Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12 hours (the amount of secondary amine is 5 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water; The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows: (1) pH adjustment: Use a 9% sodium carbonate solution to adjust the pH value of the nickel-based superalloy electrochemical solution to 0; (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the nickel-based high-temperature alloy electrochemical solution with a pH value of 0 to obtain a molybdenum adsorption solution; then, the modified MTS9570 resin is eluted with a sulfuric acid solution (pH = 2) as an eluent to obtain a molybdenum eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical solution; then, the modified MTS9570 resin after elution is desorbed with a 10% ammonia aqueous solution to obtain a molybdenum desorption solution, which is then sent for evaporation and crystallization treatment; The amount of sulfuric acid solution is 5 times the volume of the resin, and the flow rate per hour is 4 times the volume of the resin (here it means if the volume of the resin is 1m 3 , then the flow rate of sulfuric acid solution is 4m 3 / h); the amount of ammonia solution is 3 times the volume of resin, and the flow rate per hour is 4 times the volume of resin; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then sulfuric acid solution (pH = 2) is used as eluent (the amount of sulfuric acid solution is 5 times the volume of the resin, and the flow rate is 4 times the volume of the resin per hour) to elute the modified MTA1721 resin to obtain rhenium eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical dissolution solution; first, ammonium sulfate and ammonia water mixture (10% wt ammonium sulfate + 0.1% wt ammonia water, 10 times the volume of the resin, and the flow rate is 2 times the volume of the resin per hour) is used for desorption to obtain a first-stage rhenium desorption liquid, which is returned to step (1); then, a 10% ammonia water solution is used for desorption (3 times the volume of the resin, 4 times the volume of the resin) to obtain a second-stage rhenium desorption liquid, which is sent for evaporation and crystallization treatment; (4) Evaporation concentration and crystallization: The obtained molybdenum desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the molybdenum desorption solution to obtain ammonium molybdate crystals and a molybdenum mother liquor; the pH value of the molybdenum mother liquor is adjusted to 0 with a sulfuric acid solution, and the process returns to step (2) of molybdenum adsorption; the obtained second-stage rhenium desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the second-stage rhenium desorption solution to obtain ammonium perrhenate crystals and a rhenium mother liquor; the pH value of the rhenium mother liquor is adjusted to 0.5 with a sulfuric acid solution, and the process returns to step (3) of rhenium adsorption; (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution of step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution of step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to produce metallic molybdenum and metallic rhenium.
[0028] After testing, the adsorption rates of modified MTS9570 resin (molybdenum resin) for molybdenum and rhenium were 94.6% and 1.3% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 4g / L, rhenium 0.03g / L.
[0029] The modified MTA1721 resin (rhenium resin) achieved adsorption rates of 97.5% for rhenium and 0.7% for molybdenum, respectively. The element concentrations in the first-stage rhenium desorption solution were 1.5 g / L for rhenium and 0.025 g / L for molybdenum. The element concentrations in the second-stage rhenium desorption solution were 18 g / L for rhenium and 5 mg / L for molybdenum.
[0030] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99995%, respectively.
[0031] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9996% and 99.999992% respectively.
[0032] Example 2 A high-temperature alloy leachate from a high-temperature alloy recycling plant, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment, contains the following main elements: nickel 60 g / L, cobalt 6.2 g / L, aluminum 7.2 g / L, chromium 4.8 g / L, rhenium 1.1 g / L, molybdenum 1.6 g / L, tantalum 20 mg / L, tungsten 640 mg / L, and hafnium 130 mg / L; Preparation method of modified MTS9570 resin: MTS9570 resin is repeatedly washed with 50-60℃ hot water. After filtration, the resin is soaked in 2mol / L sulfuric acid for 2 hours (the amount of sulfuric acid used is 3 times the volume of the resin), washed with distilled water until the effluent water is nearly neutral, then soaked in 2mol / L phosphoric acid solution for 12 hours (the amount of phosphoric acid solution used is 3 times the volume of the resin), and washed with distilled water until the pH of the effluent water is 6, and the water is drained; Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12 hours (the amount of secondary amine is 3 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water; The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows: (1) pH adjustment: Use 9% sodium carbonate solution to adjust the pH value of the nickel-based high-temperature alloy electrochemical dissolution solution to pH = 1.0; (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the nickel-based high-temperature alloy electrochemical solution with a pH value of 1.0 to obtain a molybdenum adsorption solution; then, the modified MTS9570 resin is eluted with a sulfuric acid solution (pH = 2) as an eluent to obtain a molybdenum eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical solution; then, the modified MTS9570 resin after elution is desorbed with a 10% ammonia aqueous solution to obtain a molybdenum desorption solution, which is sent for evaporation and crystallization treatment; The amount of sulfuric acid solution used is 5 times the volume of resin, and the flow rate per hour is 4 times the volume of resin; the amount of ammonia solution used is 3 times the volume of resin, and the flow rate per hour is 2 times the volume of resin; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 1.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then, sulfuric acid solution (pH = 2) is used as eluent (wherein, the amount of sulfuric acid solution is 5 times the volume of the resin, and the flow rate is 4 times the volume of the resin per hour) to elute the modified MTA1721 resin to obtain rhenium eluent, and return to step (1); first, use ammonium sulfate and ammonia water mixture (10% wt ammonium sulfate + 0.1% wt ammonia water, 10 times the volume of the resin, and the flow rate is 1 times the volume of the resin per hour) for desorption to obtain a first-stage rhenium desorption liquid, return to step (1) and mix with nickel-based high-temperature alloy electrochemical dissolution liquid; then use ammonia water solution with a mass concentration of 10% (3 times the volume of the resin, 2 times the volume of the resin) for desorption to obtain a second-stage rhenium desorption liquid, and send it for evaporation and crystallization treatment; (4) Evaporation and concentration, crystallization: The obtained molybdenum desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the molybdenum desorption solution to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 1.0 with a sulfuric acid solution, and the process returns to step (2) of molybdenum adsorption; the obtained second-stage rhenium desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the second-stage rhenium desorption solution to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 1.5 with a sulfuric acid solution, and the process returns to step (3) of rhenium adsorption; (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution of step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution of step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to produce metallic molybdenum and metallic rhenium.
[0033] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) adsorption process were 95.2% and 0.8% respectively, and the element concentrations in the molybdenum desorption solution were: molybdenum 5.2g / L, rhenium 0.046g / L.
[0034] The modified MTA1721 resin (rhenium resin) achieved adsorption rates of 96.5% for rhenium and 0.3% for molybdenum, respectively. The element concentrations in the first-stage rhenium desorption solution were 1.1 g / L for rhenium and 0.065 g / L for molybdenum. The element concentrations in the second-stage rhenium desorption solution were 12 g / L for rhenium and 2 mg / L for molybdenum.
[0035] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99997%, respectively.
[0036] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9994% and 99.999993% respectively.
[0037] Example 3 A high-temperature alloy leachate containing rhenium and molybdenum waste liquid from a smelter, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment: 40g / L cobalt, 1.2g / L aluminum, 1.8g / L chromium, 0.78g / L rhenium, 0.6g / L molybdenum, and 640mg / L tungsten; Preparation method of modified MTS9570 resin: MTS9570 resin is repeatedly washed with 50-60℃ hot water. After filtration, the resin is soaked in 2mol / L sulfuric acid for 2 hours (the amount of sulfuric acid is 4 times the volume of the resin), washed with distilled water until the effluent water is nearly neutral, then soaked in 2mol / L phosphoric acid solution for 12 hours (the amount of phosphoric acid solution is 4 times the volume of the resin), and washed with distilled water until the pH of the effluent water is 6, and the water is drained; Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12 hours (the amount of secondary amine is 4 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water; The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows: (1) pH adjustment: Use 9% sodium carbonate solution to adjust the pH value of the nickel-based high-temperature alloy electrochemical dissolution solution to pH = 1.5; (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the electrochemical solution of nickel-based high-temperature alloy with a pH value of 1.5 to obtain a molybdenum adsorption solution; then, sulfuric acid solution (pH = 2) is used as an eluent (wherein, the amount of sulfuric acid solution is 5 times the volume of the resin and the flow rate is 4 times the volume of the resin per hour) to elute the modified MTS9570 resin to obtain a molybdenum eluent, which is returned to step (1) and mixed with the electrochemical solution of nickel-based high-temperature alloy; then, the modified MTS9570 resin after elution is desorbed with a 10% ammonia solution to obtain a molybdenum desorption solution, which is sent for evaporation and crystallization treatment; The amount of sulfuric acid solution used is 5 times the volume of resin, and the flow rate per hour is 4 times the volume of resin; the amount of ammonia solution used is 3 times the volume of resin, and the flow rate per hour is 2 times the volume of resin; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption solution is adjusted to 0.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then, sulfuric acid solution (pH = 2) is used as an eluent to elute the modified MTA1721 resin to obtain a rhenium eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical dissolution solution; First, desorb with a mixture of ammonium sulfate and ammonia water (10% wt ammonium sulfate + 0.1% wt ammonia water, 10 times the volume of the resin, 1 times the volume of the resin per hour) to obtain a first-stage rhenium desorption solution, and return to step (1); then desorb with a 10% ammonia water solution (3 times the volume of the resin, 2 times the volume of the resin) to obtain a second-stage rhenium desorption solution, which is sent for evaporation and crystallization treatment; (4) Evaporation and concentration, crystallization: The obtained molybdenum desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the molybdenum desorption solution to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 1.5 with a sulfuric acid solution, and the process returns to step (2) for molybdenum adsorption; the obtained second-stage rhenium desorption solution is evaporated and concentrated at 120°C to 1 / 3 of the volume of the second-stage rhenium desorption solution to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 0.5 with a sulfuric acid solution, and the process returns to step (3) for rhenium adsorption; (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution of step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution of step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to prepare metallic molybdenum and metallic rhenium.
[0038] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) adsorption process were 97% and 0.2% respectively, and the element concentrations in the molybdenum desorption solution were: molybdenum 1.7g / L, rhenium 0.016g / L.
[0039] The modified MTA1721 resin (rhenium resin) achieved adsorption rates of 94% for rhenium and 0.32% for molybdenum, respectively. The element concentrations in the first-stage rhenium desorption solution were 0.2 g / L for rhenium and 0.042 g / L for molybdenum. The element concentrations in the second-stage rhenium desorption solution were 8.7 g / L for rhenium and 2 mg / L for molybdenum.
[0040] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99994%, respectively.
[0041] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.99999% and 99.9999996% respectively.
[0042] The only difference between Comparative Example 1 and Example 1 is that unmodified MTS9570 resin and unmodified TA1721 resin are used, and the rest are the same as Example 1.
[0043] After testing, the adsorption rates of molybdenum and rhenium in the unmodified MTS9570 resin (molybdenum resin) during the adsorption process were 87.1% and 10.3%, respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 3.4g / L, and rhenium 0.45g / L.
[0044] The adsorption rates of unmodified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 81.6% and 4.8%, respectively. The element concentrations in the first-stage rhenium desorption solution were 1.2 g / L rhenium and 0.095 g / L molybdenum. The element concentrations in the second-stage rhenium desorption solution were 15.4 g / L rhenium and 27 mg / L molybdenum.
[0045] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 97.14% and 96.05%, respectively.
[0046] The only difference between Comparative Example 2 and Example 1 is that in step (1), the pH value of the nickel-based high-temperature alloy electrochemical dissolution solution is adjusted to 3 using 9% sodium carbonate solution, and the rest is the same as Example 1.
[0047] After testing, the adsorption rates of modified MTS9570 resin (molybdenum resin) for molybdenum and rhenium were 67.4% and 1.1% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 3.1g / L, rhenium 0.025g / L.
[0048] The modified MTA1721 resin (rhenium resin) achieved adsorption rates of 65.1% for rhenium and 0.52% for molybdenum, respectively. The element concentrations in the first-stage rhenium desorption solution were 1.0 g / L for rhenium and 0.02 g / L for molybdenum. The element concentrations in the second-stage rhenium desorption solution were 11 g / L for rhenium and 12 mg / L for molybdenum.
[0049] The adsorption rate of rhenium and molybdenum is low and the effect is poor.
[0050] The difference between Comparative Example 3 and Example 1 is that step (3) does not include the step of performing a one-stage rhenium desorption using an ammonium sulfate and ammonia aqueous solution, that is, only a 10% ammonia aqueous solution is used for desorption, and the rest is the same as in Example 1; The test results show that the element concentrations in the first stage rhenium desorption solution are: rhenium 1.4g / L, molybdenum 5mg / L. The element concentrations in the second stage rhenium desorption solution are: rhenium 17.5g / L, molybdenum 0.022g / L.
[0051] The purity of the ammonium rhenate crystals obtained after recrystallization is only 99.04%.
[0052] The only difference between Comparative Example 4 and Example 1 is that the order of step (2) and step (3) is reversed, i.e., the modified MTA1721 resin is first used for adsorption, and then the modified MTS9570 resin is used for adsorption. The other steps are the same as those in Example 1. Testing revealed that the modified MTA1721 resin (rhenium resin) exhibited adsorption rates of 91.4% for rhenium and 17.4% for molybdenum, respectively. The concentrations of the first-stage rhenium desorption solution were 1.41 g / L for rhenium and 0.76 g / L for molybdenum. The concentrations of the second-stage rhenium desorption solution were 15.2 g / L for rhenium and 87 mg / L for molybdenum.
[0053] The adsorption rates of modified MTS9570 resin (molybdenum resin) for molybdenum and rhenium were 94.6% and 0.1%, respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 2.4g / L, rhenium 0.02g / L.
[0054] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 84.6673%, respectively.
[0055] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9993% and 85.782% respectively.
[0056] The above are merely specific embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution, characterized in that: Specific steps as follows: (1) Adjusting pH: Using sodium carbonate solution to adjust the pH value of the rhenium-molybdenum solution to 0-1.5; (2) Molybdenum resin adsorption / desorption: The rhenium-containing molybdenum solution adjusted to pH value in step (1) is adsorbed by using a modified MTS9570 resin, wherein the modified MTS9570 resin is obtained by modifying the MTS9570 resin with a sulfuric acid and phosphoric acid solution, and a molybdenum adsorption liquid is obtained; then, the modified MTS9570 resin is eluted with a sulfuric acid solution as an eluent to obtain a molybdenum eluent, which is returned to step (1) to the rhenium-containing molybdenum solution; Then, the modified MTS9570 resin after elution is desorbed with an ammonia solution to obtain a molybdenum desorption solution; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5-1.5 with sulfuric acid solution, and the modified MTA1721 resin is adsorbed thereon, wherein the MTA1721 resin is obtained by modifying the MTA1721 resin with secondary amine; then the modified MTA1721 resin is eluted with sulfuric acid solution as eluent to obtain rhenium eluent, and the solution is returned to step (1) to the rhenium-containing molybdenum solution; the modified MTA1721 resin after elution is first desorbed with a mixed solution of ammonium sulfate and ammonia water, wherein the mass concentration of ammonium sulfate in the mixed solution of ammonium sulfate and ammonia water is 10% and the mass concentration of ammonia water is 0.1%, to obtain a first-stage rhenium desorption liquid, and the solution is returned to step (1); the modified MTA1721 resin after the first-stage desorption is then desorbed with an ammonia solution to obtain a second-stage rhenium desorption liquid; (4) Evaporation concentration and crystallization: The molybdenum desorption solution obtained in step (2) is evaporated and concentrated to 1 / 3 of the volume of the molybdenum desorption solution at 120° C. to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 0-1.5 and returned to step (2) to the rhenium-containing molybdenum solution with adjusted pH value; the second-stage rhenium desorption solution obtained in step (3) is evaporated and concentrated to 1 / 3 of the volume of the second-stage rhenium desorption solution at 120° C. to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 0.5-1.5 and returned to the solution after the molybdenum absorption in step (3); (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; the secondary crystallized ammonium molybdate mother liquor is returned to the molybdenum desorption liquid in step (4); the secondary crystallized ammonium rhenate mother liquor is returned to the second-stage rhenium desorption liquid in step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, and hydrogen is introduced for high-temperature calcination at a temperature of 650°C to prepare metallic molybdenum and metallic rhenium.
2. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, wherein: The preparation process of the modified MTS9570 resin is as follows: the cleaned MTS9570 resin is soaked in sulfuric acid for 2 hours, washed with distilled water until the discharged water is close to neutral, then soaked in phosphoric acid solution for 12 hours, washed with water until the pH of the discharged water is 6, and drained.
3. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 2, characterized in that: The concentration of the sulfuric acid is 2 mol / L, and the amount of the sulfuric acid used is 3-5 times the volume of the resin; the concentration of the phosphoric acid solution is 2 mol / L, and the amount of the phosphoric acid solution used is 3-5 times the volume of the resin.
4. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The preparation process of the modified MTA1721 resin is as follows: soaking the cleaned MTA1721 resin in a secondary amine for 12 hours, washing with water until the discharged water is neutral, and draining the water.
5. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 4, characterized in that: The amount of the secondary amine used is 3-5 times the volume of the resin.
6. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The rhenium-molybdenum-containing solution is a nickel-based high-temperature alloy electrochemical dissolution solution.
7. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The mass concentration of the ammonia solution in step (2) and step (3) is 10%; the amount of the ammonia solution is 3 times the volume of the desorbed resin, and the hourly flow rate of the ammonia solution is 2-4 times the volume of the resin.
8. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, wherein: In step (2) and step (3), the pH of the eluting solution of sulfuric acid is 2; the amount of sulfuric acid solution is 5 times the volume of the resin to be eluted, and the hourly flow rate of the sulfuric acid solution is 4 times the volume of the resin.
9. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The dosage of the ammonium sulfate and ammonia water mixed solution is 10 times the volume of the MTA1721 resin, and the hourly flow rate of the ammonium sulfate and ammonia water mixed solution is 1-2 times the volume of the resin.
10. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: In step (1), the mass concentration of the sodium carbonate solution is 9%, and in steps (3) and (4), a sulfuric acid solution is used to adjust the pH value.
Citation Information
Patent Citations
Method for extracting rhenium from eluate of flue ash generated by baking enriched ore of molybdenum
CN101050489A
Method for recovering rhenium from high-temperature alloy pickle liquor
CN103789552A
Selective Recovery of Rare Earth Metals From an Acidic Slurry or Acidic Solution
US20190078175A1
Cited By
Method for selectively enriching and separating molybdenum and rhenium by using zirconium-based adsorbent
CN120158611A
Method for comprehensively recovering valuable metal from high-temperature alloy
CN120230915A
A method for comprehensive recovery of valuable metals from high-temperature alloys
CN120230915B
